2018
DOI: 10.1002/cad.20238
|View full text |Cite
|
Sign up to set email alerts
|

Future Orientation in Cultural Transition: Acculturation Strategies of Youth From Three Minority Groups in Israel

Abstract: Using adolescents' narratives and survey data presented in earlier studies, we draw upon Berry's model of four acculturation strategies () to examine adolescents' narratives regarding the future orientation domains of education-and-career and marriage-and-family (Seginer, ) by three groups of nonimmigrant minority adolescents in Israel: Muslim, Druze, and ultra-Orthodox Jewish. The narratives of adolescents from the three communities studied here illustrate modified assimilation for education-and-career and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Examining parents' role in the context of Arab society and female adolescents in particular is important, since in Palestinian Arab society, the family is the main source of social support and emotional ties (Sherer & Karnieli-Miller, 2007). Despite various modernization processes, familism continues to be a central characteristic of this society (N. Haj-Yahia & Lavee, 2018;Seginer & Mahajna, 2018), especially among female adolescents, who have been shown to feel more connected to their parents (Dwairy et al, 2006) and who report receiving more parental support than do males (Khoury-Kassabri, 2019). Khoury-Kassabri, 2019 found that among Arab youth in Israel, parental relationships moderate the effect of impulsivity and other risk factors on adolescents' involvement in violence.…”
Section: Closeness To Parents As a Moderatormentioning
confidence: 99%
“…Examining parents' role in the context of Arab society and female adolescents in particular is important, since in Palestinian Arab society, the family is the main source of social support and emotional ties (Sherer & Karnieli-Miller, 2007). Despite various modernization processes, familism continues to be a central characteristic of this society (N. Haj-Yahia & Lavee, 2018;Seginer & Mahajna, 2018), especially among female adolescents, who have been shown to feel more connected to their parents (Dwairy et al, 2006) and who report receiving more parental support than do males (Khoury-Kassabri, 2019). Khoury-Kassabri, 2019 found that among Arab youth in Israel, parental relationships moderate the effect of impulsivity and other risk factors on adolescents' involvement in violence.…”
Section: Closeness To Parents As a Moderatormentioning
confidence: 99%
“…Despite such gender differences in future planning and academic achievement, the gender differences in the reciprocal effects of the two constructs have been scarcely explored in prior research. Previous studies on the relations between future planning and academic achievement have predominantly included only Western female samples (e.g., Hejazi et al, 2011;Seginer & Mahajna, 2018) or have reported mixed results (e.g., Scholtens, Rydell, & Yang-Wallentin, 2013). Only recently has research on identity development begun to take into account gender differences in the reciprocal effects on exploration, commitment and academic achievement.…”
Section: Gender Differencesmentioning
confidence: 99%
“…Third, based on Nurmi's theory of future orientation (Nurmi, 1991) and few previous studies (Khir & Redzuan, 2017;Pintrich & Schunk, 1996), we hypothesized that there would be positive reciprocal relations between affects concerning the future and academic achievement. Fourth, based on previous studies (Hejazi et al, 2011;Pop et al, 2015;Seginer & Mahajna, 2018;Solantaus, 1987;Steinberg et al, 2009;Trommsdorff et al, 1978), it was anticipated that the reciprocal relations between future planning and academic achievement would be different for boys and girls, and for younger and older adolescents.…”
Section: The Present Studymentioning
confidence: 99%
“…There was still a lack, and limited publication about student minority groups refers to religion at school compare to racial and ethnicity. One publication found was written by Seginer & Mahajna, (2018) addressed about the acculturation strategies of youth from three religion minority groups in Israel namely Muslim, Druze, and ultra-Orthodox Jewish. Seemingly, there were many parties still did not understand the role and function of religious education in schools.…”
Section: Introductionmentioning
confidence: 99%